2007
DOI: 10.5964/ijpr.v1i2.11
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Everyday Hate: A Qualitative and Quantitative Analysis

Abstract: Throughout history artists, poets, and writers have been interested in the nature of hate. Scientists from a variety of disciplines have also attempted to unravel its mysteries. Yet in spite of abundant theorizing and research, most modern scholars still complain that little is known about this complex emotion. In this study, a new approach has been taken. Following Heider's (1958) observation that scientists can often learn a great deal by exploring people's "common-sense" or "naïve psychologies," students at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 64 publications
1
25
0
1
Order By: Relevance
“…Most authors who have written on hate agree that it is a powerful negative emotional phenomenon (Aumer-Ryan & Hatfield, 2007; Royzman et al, 2005; Sternberg, 2003), although not all scholars would define it as an emotion. Hate is assumed to develop when others mistreat or humiliate someone, or whose deliberate actions have become an obstruction to someone’s goals (Aumer-Ryan & Hatfield, 2007; Baumeister & Butz, 2005; Royzman et al, 2005; Sternberg, 2003). Hate obviously shares characteristics with several other negative emotions, especially anger, contempt, or moral disgust (Fitness & Fletcher, 1993; Frijda, 1986; Halperin, 2008; Oatley & Jenkins, 1996).…”
Section: What Are the Characteristics Of Hate?mentioning
confidence: 99%
See 2 more Smart Citations
“…Most authors who have written on hate agree that it is a powerful negative emotional phenomenon (Aumer-Ryan & Hatfield, 2007; Royzman et al, 2005; Sternberg, 2003), although not all scholars would define it as an emotion. Hate is assumed to develop when others mistreat or humiliate someone, or whose deliberate actions have become an obstruction to someone’s goals (Aumer-Ryan & Hatfield, 2007; Baumeister & Butz, 2005; Royzman et al, 2005; Sternberg, 2003). Hate obviously shares characteristics with several other negative emotions, especially anger, contempt, or moral disgust (Fitness & Fletcher, 1993; Frijda, 1986; Halperin, 2008; Oatley & Jenkins, 1996).…”
Section: What Are the Characteristics Of Hate?mentioning
confidence: 99%
“…The enduring nature of hatred is based in the appraisals that are targeted at the fundamental nature of the hated group. Given that hate is often not a reaction to a specific event, and not limited to a short period of time, the question is raised whether hate actually is an emotion, or rather an emotional attitude or sentiment (Allport, 1954; Aumer-Ryan & Hatfield, 2007; Frijda, 1986; Frijda, Mesquita, Sonnemans, & van Goozen, 1991; Halperin et al, 2012; Royzman et al, 2005; Shand, 1920, as cited in Royzman et al, 2005; Sternberg, 2005). In the last two decades, scholars (e.g., Fischer & Giner-Sorolla, 2016; Halperin, 2008; Sternberg, 2003) have resolved this contradiction between emotions and sentiments by suggesting that some “emotions” can occur in both configurations—immediate and chronic, and thus can be conceived of as a (short-term) emotion as well as a (long-term) sentiment.…”
Section: What Are the Characteristics Of Hate?mentioning
confidence: 99%
See 1 more Smart Citation
“…Some empirical research has validated this close association between love and hate. For example, Zeki and Romaya (2008) found that similar areas in the brain (i.e., the putamen and insula) are involved with both love and hatred, and Aumer-Ryan and Hatfield (2007) found that hatred is often directed at those we have loved (e.g., former/current romantic partners), know well (e.g., friends and family), or spend considerable time with (e.g., coworkers, bosses, competitors).…”
mentioning
confidence: 99%
“…Considering previous research has shown that the targets of one's hatred are often those we love or have loved (Aumer, Bahn, & Harris, 2015;Aumer-Ryan & Hatfield, 2007), the following studies are designed to better understand how previous feelings of hatred towards someone loved can affect the relationship. This research will answer the following questions: Does having hate in a relationship (e.g., friendship, towards a spouse, or a co-worker) damage the relationship or can it bolster the relationship, once the hatred has resolved?…”
mentioning
confidence: 99%